Community Driven Open Science - O’Connor, Brian (Septentrio Conference Series, 2014)
>> See video of presentation (23 min.) The Royal Society of Chemistry is committed to supporting open science in the UK and at a global level. Our recently launched Chemical Sciences Article Repository provides a subject-specific repository for hosting research outputs, including ‘green’ open access articles from our own authors, and published ‘gold’ articles. We are working with institutional repositories and other publishers to include links to articles on their own sites, ensuring maximum visibility and usage of their own content. Our aim is to ensure compliance with open access mandates is as simple as possible for researchers in the chemical sciences and related disciplines. This complements our Gold for Gold initiative launched in 2012. We plan to expand the Chemical Sciences Repository to include other types of publications, research data and tools. Currently we are building a data repository for the UK academic community as part of our EPSRC funding for hosting the National Chemical Database Service (an EPSRC mid-range facility). This will allow researchers to deposit, access and share data, but allow the flexibility to only share data privately if preferred. Using our expertise from developing ChemSpider, our flagship free chemical database, search functionality and accessibility of the data within the repository will be optimised for the chemical scientist.